A Study on the Evaluation of High-Quality Development of Enterprises in the Context of Digital Transformation: A Case Study of Hualing Steel - Weiman Zheng; Haojie Liao; Bifang Huang; kangqiao Xu (Journal of Frontier in Economic and Management Research, 2025)
In the context of the digital economy, digital transformation of enterprises has become a current hot topic. This study focuses on Hualing Steel to explore how enterprises can achieve high-quality development through digital transformation. The paper employs indicators of efficiency, innovation, and green development, utilizing the entropy and TOPSIS methods to quantitatively assess transformation performance from 2013 to 2023. The analysis yields three key conclusions: (1) Digital transformation has yielded significant outcomes, with the highest comprehensive performance observed in 2021, coinciding with the launch of the 5G smart factory; (2) A structural characteristic of "efficiency improvement leading, with innovation-driven development lagging" is identified; (3) Recommendations are made for deepening the application of digital technologies, optimizing enterprise operation management systems, enhancing innovation-driven development, and improving talent development systems. These findings provide a theoretical framework and practical model for the transformation and upgrading of traditional manufacturing industries.